Employee behavior in employee stock option plans: Why do some employees acquire company stock?. Issue 2 (8th September 2022) - Pendleton, Andrew; Robinson, Andrew
Abstract: The article focuses on decisions to exercise and hold company stock at the maturity of a broad‐based employee stock options plan. It investigates why some participants choose an uncertain and risky future reward when an immediate and certain increase in wealth could be secured at exercise. It draws on and expands the "mixed gambles" perspective in behavioral agency theory, utilizing a combination of stock price data and employee survey data from British companies with tax‐approved stock option plans. It is found that the decision to take a gamble is influenced (negatively) by the extent of stock price lows (relative to prices at exercise) in the year prior to exercise, and by the risk preferences of the option holder. The findings contribute to further development of the "mixed gambles" perspective as an explanation of stock option behavior, showing that individual characteristics as well as some stock price movements affect behavior.